Factors Affecting the Adoption of Information Technology Applications in the Food Service Sector in Malaysia - Ismail, Ahmad Fareed (2008)
In recent years, many organizations have invested tremendously in information technology (IT) aiming to improve their firms7 performance. Previous literature suggest that various factors play crucial roles in the adoption of information systems. However, there is little empirical research about the factors affecting the adoption of IT applications in the foodservice sector. This study aims to determine the factors affecting the adoption of IT applications (specifically on the back-of-house and front-of-house IT applications) in the foodservice sector. The research model posits relationships of three major factor groups; a) the organizational factor group, b) environmental factor group, and c) technological factor group. Under these three factor groups there are ten factors to be tested against the adoption decision of the two foodservice IT applications. The factors are 1) top management support, 2) organizational size, 3) relative advantage, 4) strategic relevance, 5) Jinancial slack, 6) IT support infrastructure, 7) competitive pressure, 8) IT skilled employees, 9) ease of use, and 10) compatibility. The theoretical model of this study is based on the Diffusion of Innovation (DOI) Theory. In this study, survey questionnaires were distributed to the Chief Executive Officers (CEO)/ or owners, or Chief Information Officers (CIO), or Management Information Systems ManagerdIT Managers, or Operation Managers or Account1 Finance Manager of the available 323 foodservice companies. The foodservice operators involved in the sampling were from restaurants belonging to foodservice chains and independent restaurants in Kuala Lumpur and Selangor. The results showed that the response rate was 49.5%. A multiple regression analysis for the adoption of back-ofhouse IT applications and multinomial logistic regressions for front-of-house IT applications were used to test the hypotheses. The results revealed that factors such as top management support, strategic relevance, financial slack, IT skilled employees, ease of use, and compatibility affected the adoption of back-of-house IT applications. However, only the relative advantage and competitive pressure were found to be significant for the adoption of front-of-house IT applications. This suggests that different segments of business operations tended to influence different factors affecting the adoption of IT applications in the foodservice industry. Therefore, the results of this study provide some theoretical and practical implications of factors affecting the adoption of IT in the foodservice sector.